Development of psychomotor reactions and dynamics of motion frequency at coaching hours - Skernevičius , J. (Psichologija, 1969)
We have observed 62 students divided into three groups in the course of three years. Students belonging to the first group attended four hours of general coaching per week during the first and second years of studies, and two hours per week in third year. Students belonging to the second group were coached in skiing eight hours per week. The third group was coached in games eight hours per week. The results of the observation show that no less than four weakly hours of coaching are effective in developing psychomotor reactions and dynamics of motion frequency. The observation has revealed that psychomotor reactions and dynamics of motion frequency are closely connected with speed.
Keywords: psychomotor reactions; dynamics of motion frequency; coaching hours